Make our people great again: people according to Latin-American progressive presidents (2005-2011) - Rosillo-Villena, Juan Carlos (Árboles y Rizomas, 2023)
The present article reports results of a critical discourse analysis of thirty-two discursive events from five Latin American progressive presidents, Cristina Fernández, Evo Morales, Michelle Bachelet, Rafael Correa y Tabaré Vásquez (2005-2011), in order to answer the research question: What are the components and strategic functions of the political discourse on the concept of people in the presidents’ speeches under study? Following the tenets of critical discourse studies, a dynamic model is introduced that includes three dimensions of analysis: a) sociohistorical, b) interpretative, and c) discourse. Results indicate that the most frequent components are descriptive and questioning, referring to the evaluation of the national situation, and prescriptive in terms of the goal of overcoming the neoliberal model. The concept of people has a legitimizing function of progressivism in the face of liberal democracy.
Keywords: critical discourse studies; progressive presidents; people; Latin America